Plasmin, plasminogen, protein and somatic cells variation of bulk milk : impact of breed, milking system and production months - Shishanthi, Jayarathna (SLU/Department of Molecular Sciences, 2017)
During a period of one year, milk samples were collected from 45 different farms in Northern Sweden. Plasmin (PL), plasminogen (PG), somatic cell count (SCC) and total protein (TP) content were investigated in bulk milk received at the dairy. The composition of bulk milk samples was related to major farm and production variables (breed, milking system and production months). SCC and TP were measured in whole milk while, PL and PG analyses were performed on serum fraction in duplicates obtained by ultracentrifugation of defatted milk. PL and PG derived activities were analyzed by spectrophotometric method using multi-mode microplate reader at 37°C. Urokinase (49.5 plough units) was used as PG activator to measure the total proteolytic activity of PL and PG. The PG derived activity was not influenced by the breed class. The farms having mixtures of breeds had higher (P < 0.05) PL activity as compared to farms having Holstein, Swedish Red and both Holstein, Swedish Red and their crosses. PL and PG derived activities had no influence (P > 0.05) from the milking system and production month for the considered farms. SCC varied with breed, lowest SCC (P < 0.05) was reported for Swedish Red breed and highest (P < 0.05) was reported for mountain breeds. Higher (P < 0.05) SCC counts were observed in AMS farms compared to CMS farms. SCC varied slightly according to the production month. Lower (P < 0.05) TP content was recorded for mountain breeds than for Holstein, Swedish red and farms having mixture of breeds. Jersey breed showed higher (P < 0.05) TP content than other breeds. Higher (P < 0.05) bulk milk TP content was observed for CMS than AMS farms. The mean TP content varied (P < 0.05) with the production month, with higher amount in October, November and December than in June, July and August. There was no clear trend or correlation of PL activity and PG derived activity with bulk milk TP or SCC.